1993
DOI: 10.1177/0148607193017006501
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Long‐Term Total Parenteral Nutrition Patients and Their Family Caregivers

Abstract: The purpose of this study was to identify individual and family variables associated with patient and caregiver quality of life. Perceived quality of life has been associated with improved outcomes and compliance. Methods included telephone interviews of 178 families, randomly selected from academic, hospital, and infusion agencies across the United States, with 116 follow-up questionnaires returned. Patients had varied bowel disorders requiring total parenteral nutrition for an average of 4.6 years. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 48 publications
3
55
1
3
Order By: Relevance
“…Health-related quality of life (HRQOL) has been studied among caregivers of patients with dementia [3][4][5][6], cancer [7][8][9][10][11][12], end stage renal disease [13], multiple sclerosis [14], and those receiving total parenteral nutrition [15]. While Reichenberg and Broberg [16] showed that the QOL of the caregivers of children with asthma was related to the severity of the asthma, Price et al [17] concluded that caregiver affect may have a considerable influence on reports of caregiver QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life (HRQOL) has been studied among caregivers of patients with dementia [3][4][5][6], cancer [7][8][9][10][11][12], end stage renal disease [13], multiple sclerosis [14], and those receiving total parenteral nutrition [15]. While Reichenberg and Broberg [16] showed that the QOL of the caregivers of children with asthma was related to the severity of the asthma, Price et al [17] concluded that caregiver affect may have a considerable influence on reports of caregiver QOL.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, QOL has been assessed rarely in adult patients receiving HPN. [5][6][7][8][9][10] To determine whether HPN, and underlying digestive disease, adversely influences QOL of children and their families, we conducted a national multicenter study involving all the pediatric HPN-authorized centers in France. We also aimed to assess factors influencing QOL of the children treated by HPN.…”
mentioning
confidence: 99%
“…Smith et al found that the overall low QOL was associated with the length of time of HPN, fewer family coping skills, and inability to get along on income, whereas higher QOL was associated with higher self-esteem and quality in the family relationship. Jeppesen et al reported that QOL is reduced in patients on HPN compared with those with anatomical or functional SBS not receiving HPN, and comparable with that reported for patients with chronic renal failure treated by dialysis [28-30, 81,82].…”
Section: Other Complicationsmentioning
confidence: 57%
“…Different investigators have reached different conclusions regarding QOL in HPN patients [81,82]. Smith et al found that the overall low QOL was associated with the length of time of HPN, fewer family coping skills, and inability to get along on income, whereas higher QOL was associated with higher self-esteem and quality in the family relationship.…”
Section: Other Complicationsmentioning
confidence: 99%